Vitamin B12 deficiency in patients with type 2 diabetes mellitus - Sekhri, Tarun; Aggarwal, Rashmi; Chugh, Pradeep; Belagavi, Shreeshail; Aggarwal, Hemant (International Journal of Advances in Medicine, 2019)
Background: Vitamin B12 deficiency may occur consequent to long-term treatment with metformin but very few studies in India have assessed this risk. Metformin is considered the drug of first choice not only for the management of type 2 diabetes but also for prediabetes and polycystic ovary disease. The study was carried out to assess the serum levels of vitamin B12 in Indian patients with type 2 diabetes mellitus who were treated with metformin for a minimum duration of five years. Methods: Serum vitamin B12 level was estimated in 39 patients with type 2 diabetes mellitus, who were on metformin for more than five years. vitamin B12 deficiency was defined as serum concentration less than 200 pg/dl. Apart from vitamin B12, fasting blood sugar, post prandial sugar and glycosylated hemoglobin were also estimated. Results: 39 subjects in age group of 40-65 years, suffering from type 2 diabetes mellitus, for more than five years were recruited for the study. The mean serum level of vitamin B12 was 153.27±46.01. Vitamin B12 deficiency was found in 35.89% subjects. Conclusions: Patients suffering from long standing type 2 diabetes mellitus and taking large doses of metformin should be screened for Vitamin B 12 deficiency.